Fluorine effects on Sr1.7Mg0.3SiO4:0. 01Eu2+, 0.08Mn2+ phosphors for white light-emitting diodes - Guo, M.; Huang, L.; Zhao, S.; Deng, D.; Wang, H.; Hua, Y.; Jia, Guohua; Xu, S. (2013)
A series of phosphors with nominal compositions of Sr1.7M 0.3SiO4-xFx:0.01Eu2+, 0.08Mn 2+ (x=0, 0.01, 0.05, 0.1, 0.2) were synthesized through solid-state reaction technique. Their luminescent properties were studied. Three emission bands with peaks at 455, 550 and 670 nm are observed in the phosphors under 380 nm light excitation. When doped with fluorine, the crystal phases of the phosphors were changed slightly, while the luminescent intensities were remarkably enhanced and colorimetric parameters (chromaticity coordinates, color rendering index and color temperature) were improved. The colorimetric parameters and thermal quenching properties of Sr1.7Mg 0.3SiO4-xFx:0.01Eu2+, 0.08Mn 2+ phosphors with the comparison with those of commercial 467 nm stimulated YAG:Ce3+ phosphors were systematically investigated. These results indicate that the phosphor with optimized composition could be a promising phosphor as a white light-emitting phosphor for near-ultraviolet light-emitting diodes. © 2012 Elsevier B.V. All rights reserved.